Analysis of the Development of the PAI Curriculum for Grade IV Elementary School from K13 to Independent Curriculum - Pramesti, Zaffa Eka; Rohali, Aderisna; Nasmu, Rafli Pasila (Jurnal Multidisiplin Indonesia, 2024)
Islamic religious education is given as a form of effort to guide students so that in the future, after learning, a person can understand and apply Islamic teachings correctly. The change that occurred from the 2013 Curriculum to the Independent Curriculum, of course happened because of the development where the development of this curriculum aims to make teaching and learning interactions between teachers and students will be more efficient and effective during the learning process. This study aims to see how the form of change in PAI subjects from the 2013 Curriculum to the Independent Curriculum. The method used in this study is literature. The results obtained from this study show that there is a difference in PAI Learning from K13 to the Independent Curriculum, namely in the use of media, methods and approaches that produce fun learning. In the PAI class IV subject, there are not many changes in the material, only how the teacher applies learning, starting from the use of fun learning methods, the use of interactive media, and the use of learning approaches that need to be adjusted to the interests and talents of students.